Review of AC-DC power electronic converter topologies for power factor correction - Rajagopal Sasikala; R. Seyezhai (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Increased harmonic content and low power factor in power systems caused by power converters have been of great concern. To overcome this, several converter topologies employing advanced semiconductor devices and control schemes have been proposed. The aim of this paper is to identify a low cost, small size, efficient and reliable ac to dc converter to meet the input performance index of uninterrupted power supply. In this paper, comparison between three converters namely AC-DC Cuk rectifier, Fly back converter & Interleaved SEPIC converter have been carried out. For the above converters both bridged and bridgeless topologies have been analysed. The working of all the three types of converter has been   illustrated with relevant waveforms followed by the simulation results. Comparison of the three converters have been done based on the parameters namely Displacement Factor, Supply Power Factor& supply THD. The results are verified.